Utilizing ChatGPT in Learning Contexts: Teachers’ Perspectives on Foreign Language Instruction Practices - Rona Adani Ulayya; Nil Andrian Afandi Matondang; Restina Liza; Muhammad Hasyimsyah Batubara (Yayasan Cerdas Pedia Indonesia, 2026)
The rapid penetration of generative artificial intelligence disrupts foreign language education, yet the underlying pedagogical rationales of teachers remain critically underexplored. This explanatory sequential mixed methods study investigated twenty foreign language educators in Medan, Indonesia, utilizing quantitative surveys followed by comprehensive thematic interviews. Findings reveal that 75 percent of participants pragmatically adopted ChatGPT to alleviate structural administrative burdens, acting as proactive innovators rather than passive users. Conversely, 25 percent demonstrated existential resistance, citing profound concerns over student cognitive deskilling and the loss of authentic learning friction. Furthermore, instructional applications evolved from basic text generation into highly complex sociolinguistic facilitation. However, systemic infrastructural disparities, absent ethical regulations, and digital divides continually threaten equitable technological adoption across learning environments. The study concludes that sustainable artificial intelligence integration directly requires transitioning from technocentric enthusiasm toward critical algorithmic literacy, necessitating robust institutional frameworks to protect professional educator autonomy and safeguard fundamental academic integrity globally.